The Influence of Digital Literacy and Entrepreneurial Self-Efficacy on Entrepreneurial Intention of University Student in West Jakarta - Juficha, Annelis Diva; Rodhiah (Journal of Social Science and Business Studies, 2026)
This research seeks to examine how digital literacy and entrepreneurial self-efficacy affect the entrepreneurial intention of undergraduate students in West Jakarta. The study is motivated by the swift advancement of digital technology, which opens various business possibilities; however, these opportunities are not always accompanied by adequate digital skills or entrepreneurial confidence among students. A quantitative descriptive approach was applied, involving 150 undergraduate participants who have completed or are currently enrolled in entrepreneurship courses. Data were gathered through an online survey and processed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that digital literacy exerts a positive and significant impact on entrepreneurial intention. In addition, entrepreneurial self-efficacy emerges as the most influential factor affecting students’ intention to engage in entrepreneurship. The study concludes that digital competencies and confidence in entrepreneurial abilities play crucial roles in determining students’ readiness to start a new venture. These results suggest that educational institutions should reinforce digital-oriented entrepreneurship curricula to better prepare younger generations for today’s evolving business environment.